Bantar Gebang Integrated Waste Disposal Study with Income, Public Health - Raston, Sitio; Sabam, Simbolon; Rr. , Dian Anggraeni; Herijawati, Etty (International Journal of Psychosocial Rehabilitation, 2020)
The importance of this research is to find out why the Village community Ciketingudik, Cikiwul and Sumurbatu, Bantar Gebang Subdistricts, refused company Bantar Gebang waste disposal and processing site. It often happens disputes on the grounds that the company / institution only caused loss to society such as pollution and environmental pollution and spreading disease. Existence Bantar Gebang landfills and waste processing areas are like two sides of a coin cause things that are not good, its existence also affects income local community. The income to be studied is the income received by the communitylocal companies / agencies in the form of health compensation, wages become employeesand income from opening businesses around waste treatment plants. The research was conducted at the Bantargebang integrated landfill with three kelurahan namely Kelurahan Ciketingudik, Cikiwul and Sumurbatu by taking samples as many as 156 respondents. Stages of research are Identifying problems, Conducting studies literature, Conducting a preliminary survey, Creating a questionnaire design, Collecting data consisting of primary data and secondary data, primary data obtained by sharing questionnaire to the public and secondary data obtained from companies / agencies related, Conduct analysis and discussion, The last to make a report on the results research. The method used in this study is descriptive to determine the effect landfills integrated towards income and public health that have been collected will be tested and analyzed using the SPSS version 23 Corruption program canonical (Canonical Correlation).The results of the study are that the Tempat Pembuangan Sampah Bantar Gebang (TPST) with respect to income and community sickness is the canonical loading figure for income Y1 community is 0.298 or 29.8% less significant while on the distribution Y2 disease in society obtained canonical loading rate of 0.977 or 97.7% meaning very significant influence of Bantar Gebang TPST on the spread of disease in the TPST location.